Balancing Work Life For Better Performance: Investigating The Moderating Effect of Family Supportive Supervisor Behavior - Ramadhan, Fajar; Kambara, Roni (PT. Maju Malaqbi Makkarana, 2025)
This study examines the effect of work-life balance on employee performance, with family supportive supervisor behavior as a moderating variable. The research was conducted at the Regional Financial and Asset Management Agency (BPKAD) of Banten Province, Indonesia, involving civil servants as respondents. This study addresses the issue of fluctuating employee performance despite repeated institutional achievements, by investigating the role of work-life balance and supervisor support in enhancing individual outcomes. A quantitative approach with a descriptive design was used, and data were collected through structured questionnaires. The results show that work-life balance positively influences employee performance. However, family supportive supervisor behavior does not significantly strengthen this relationship, indicating that while supervisor support is appreciated, it may not be sufficient in the absence of broader organizational support systems. These findings highlight the importance of implementing formal work-life policies and promoting a supportive work culture to improve employee well-being and performance in public institutions.